Characterizations of derivations on spaces of smooth functions - Fechner, Włodzimierz; Świątczak, Aleksandra (Aequationes mathematicae, 2023)
We provide a list of equivalent conditions under which an additive operator acting on a space of smooth functions on a compact real interval is a multiple of the derivation.